Physiological Evaluation of Cooling Devices in Conjunction With Personal Protective Ensembles Recommended for Use in West Africa. (17th March 2017) - Quinn, Tyler; Kim, Jung-Hyun; Strauch, Amanda; Wu, Tianzhou; Powell, Jeffery; Roberge, Raymond; Shaffer, Ronald; Coca, Aitor
Abstract: Objective: Cooling devices (CDs) worn under personal protective equipment (PPE) can alleviate some of the heat stress faced by health care workers responding to the Ebola outbreak in West Africa. Methods: Six healthy, young individuals were tested while wearing 4 different CDs or no cooling (control) under PPE in an environmental chamber (32°C/92% relative humidity) while walking (3 METs, 2.5 mph, 0% grade) on a treadmill for 60 minutes. Exercise was preceded by a 15-minute stabilization period and a 15-minute donning period. Results: The control condition resulted in a significantly higher rectal temperature (Tre ) at the end of the exercise than did all CD conditions (CD1, P =0.004; CD2, P =0.01; CD3, P =0.000; CD4, P =0.000) with CD1 and CD2 resulting in a higher Tre than CD3 and CD4 ( P <0.05). The control condition resulted in a higher heart rate (HR) at the end of exercise than did the CD3 ( P =0.01) and CD4 ( P =0.009) conditions, whereas the HR of the CD1 and CD2 conditions was higher than that of the CD3 and CD4 conditions ( P <0.05). Weight loss in the control condition was higher than in the CD3 ( P =0.003) and CD4 ( P =0.01) conditions. Significant differences in subjective measurements of thermal stress were found across conditions and time. Conclusions: Use of CDs can be advantageous in decreasing the negative physiological and subjective responses to the heat stress encountered by health care workers wearing PPE in hot and humid environments. ( Disaster Med Public Health Preparedness . 2017;11:573–579)